A catechol oxidase AcPPO from cherimoya (Annona cherimola Mill.) is localized to the Golgi apparatus. (January 2018) - Olmedo, Patricio; Moreno, Adrián A.; Sanhueza, Dayan; Balic, Iván; Silva-Sanzana, Christian; Zepeda, Baltasar; Verdonk, Julian C.; Arriagada, César; Meneses, Claudio; Campos-Vargas, Reinaldo
Highlights: AcPPO:GFP co-localizes with a Golgi apparatus marker in Nicotiana benthamiana leaves. Peak AcPPO activity correlates with Golgi apparatus marker activity. AcPPO faces the lumen of Golgi apparatus vesicles. Abstract: Cherimoya ( Annona cherimola ) is an exotic fruit with attractive organoleptic characteristics. However, it is highly perishable and susceptible to postharvest browning. In fresh fruit, browning is primarily caused by the polyphenol oxidase (PPO) enzyme catalyzing the oxidation of o-diphenols to quinones, which polymerize to form brown melanin pigment. There is no consensus in the literature regarding a specific role of PPO, and its subcellular localization in different plant species is mainly described within plastids. The present work determined the subcellular localization of a PPO protein from cherimoya (AcPPO). The obtained results revealed that the AcPPO- green fluorescent protein co-localized with a Golgi apparatus marker, and AcPPO activity was present in Golgi apparatus-enriched fractions. Likewise, transient expression assays revealed that AcPPO remained active in Golgi apparatus-enriched fractions obtained from tobacco leaves. These results suggest a putative function of AcPPO in the Golgi apparatus of cherimoya, providing new perspectives on PPO functionality in the secretory pathway, its effects on cherimoya physiology, and the evolution of this enzyme.